Impact of aerobic training with and without whole-body vibration training on metabolic features and quality of life in non-alcoholic fatty liver disease patients - YAĞCI, İLKER; YILMAZ, YUSUF (MASSON EDITEUR, 2020)
The present study examined the effectiveness of adding exercises with whole-body vibration (WBV) to aerobic training in terms of metabolic features and quality of life. Patients with non-alcoholic fatty liver disease (NAFLD), confirmed on imaging, underwent an 8-week individualized exercise program randomized between aerobic training with and without WBV. Training was performed at 60-80% heart rate workload for 165 min/week. The WBV amplitude was 2-4 mm and the training frequency was 30 Hz, for 15 min. Assessments were carried out on surrogate scores of steatosis and fibrosis including transient elastography (FibroScan), metabolic features (biochemical analysis) and quality of life (SF-36). Insulin resistance was markedly reduced ( -2.36; 95% CI: -4.96 to -0.24; P: 0.049) in aerobic training with WBV. The decrease in serum aspartate transaminase was significantly greater in aerobic training without WBV ( -14.81; 95% CI: -23.36 to -6.25; P: 0.029). There were no significant differences between groups for the other metabolic features (P< 0.05). All quality of life well-being domains improved in both groups (P< 0.05). Given this reduction in insulin resistance, WBV can usefully be added to aerobic training. However, WBV did not provide further benefits in improving metabolic properties or quality of life. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Acceleration; Exercise; Metabolic features; Non-alcoholic fatty liver disease; Well-being; TRANSIENT ELASTOGRAPHY; PHYSICAL-ACTIVITY; EXERCISE; STEATOHEPATITIS; REHABILITATION; ASSOCIATION; PERFORMANCE; PREVENTION; RESISTANCE; PARAMETER